Analisis Kinerja Keuangan Pada Lembaga Perkreditan Desa (Lpd) Desa Adat Tabanan - Ida Ayu Agung Idawati; Ni Gusti Ayu Agung Trisna Putri (Fakultas Ekonomi Universitas Warmadewa, 2019)
Village Credit Institutions are financial institutions operating in every Pakraman village in Bali. The sustainability of a Village Credit Institution depends on the trust of the community, and thus their existence is expected to be able to maintain the trust of the people who invest their funds in the institution. Financial performance is one indicator of the assessment of the development of a Village Credit Institution. The purpose of this study was to assess the financial performance of the Village Credit Institution in Tabanan from 2011- 2015. The assessment techniques used in this study were liquidity ratio analysis, activity ratio analysis, solvability ratio analysis, profitability ratio analysis, efficiency analysis business, and statistical analysis using historical ratio standards. The results show that the liquidity ratio (current ratio) in 2011 is considered very good; in 2012, 2013, 2014 it was considered good enough,; while in 2015 it was considered less. The activity ratio (total assets turn over) in 2011, 2013, 2014 and 2015 is considered to be quite good while 2012 is considered not good enough. The solvability ratio (debt to assets ratio) in 2011 is considered not good enough, in 2012, 2013 and 2014 it is considered good enough, but in 2015 it is considered very good. The rentability ratio with the economic rentability in 2011 and in 2015 is considered very good, but in 2012, 2013, 2014 it is considered quite good. Rentability of own capital in 2011, 2012, 2013 and 2014 is considered good enough, but in 2015 it is considered very good. The business efficiency (leverage multiplier) in 2011 is considered to be less efficient, in 2012, 2013, 2014 it is considered quite efficient, but in 2015 is considered very efficient. Lembaga perkreditan desa adalah lembaga keuangan yang beroperasi di setiap desa pakraman di bali. Keberlanjutan hidup suatu LPD bergantung pada kepercayaan masyarakat, sehingga tiap-tiap LPD yang ada di Bali diharapkan mampu menjaga serta mempertahankan kepercayaan masyarakat yang menanamkan dananya pada lembaga tersebut. Kinerja keuangan merupakan salah satu indikator penilaian perkembangan suatu Lembaga Perkreditan Desa. Tujuan penelitian ini adalah untuk menganalisis kinerja keuangan pada Lembaga Perkreditan Desa (LPD) Desa Adat Tabanan dari tahun 2011–2015. Teknik analisis yang digunakan dalam penelitian ini adalah analisis rasio likuiditas, analisis rasio aktivitas, analisis rasio solvabilitas, analisis rasio rentabilitas, analisis efisiensi usaha dan analisis statistik dengan menggunakan standar rasio historis Rasio likuiditas (rasio lancar) pada tahun 2011 menunjukkan sangat baik, pada tahun 2012, 2013, 2014 dianggap cukup baik, sedangkan pada tahun 2015 dianggap kurang. Rasio aktivitas (total assets turn over) pada tahun 2011, 2013, 2014 dan 2015 dianggap 2012 cukup baik sementara dianggap belum cukup baik. Rasio solvabilitas (debt to asset ratio) pada tahun 2011 dianggap kurang baik, pada tahun 2012, 2013 dan 2014 dianggap sangat baik. Rentability ratio dengan menggunakan rentabilitas ekonomi pada tahun 2011 dan 2015 dianggap sangat baik, sedangkan pada tahun 2012, 2013, 2014 dianggap cukup baik. Rentabilitas modal sendiri pada tahun 2011, 2012, 2013 dan 2014 dianggap cukup baik, sedangkan pada tahun 2015 dianggap sangat baik. Efisiensi bisnis (leverage multiplier) pada tahun 2011 dianggap kurang efisien, pada tahun 2012, 2014 dianggap cukup efisien, sedangkan pada tahun 2015 dianggap sangat efisien.